2015
DOI: 10.3390/molecules200815033
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cytosolic Phospholipase A2α (cPLA2α) by Medicinal Plants in Relation to Their Phenolic Content

Abstract: Abstract:The cytosolic phospholipase A 2 α (cPLA 2 α) is one of the potential targets for anti-inflammatory drugs, since this enzyme plays a key role in the inflammation processes seen in health disorders, like asthma, allergic reactions, arthritis and neuronal diseases. In this study, cPLA 2 α inhibition by 43 methanol extracts from medicinal plants rich in polyphenols was determined. The eight most active extracts were derived from Ribes nigrum (IC 50 of 27.7 µg/mL), Ononis spinosa (IC 50 of 39.4 µg/mL), Urt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
2
4
0
Order By: Relevance
“…The development of E. coli colonies was inhibited by RP and OS and was stimulated by CV and MO (RP ↓ > OS ↓ > CV ↑ > MO ↑). The good antibacterial effect against E. coli was also demonstrated [30,32] for RP and MO [50]. In the case of MO, a medium effect on E. coli was observed [51], while our studies are supported by Ferrente et al (2020) [15], who proved a promising effect of OS on three E. coli strains, with concentrations ranging from 31-250 µg/mL.…”
Section: Antimicrobial Activitysupporting
confidence: 85%
See 1 more Smart Citation
“…The development of E. coli colonies was inhibited by RP and OS and was stimulated by CV and MO (RP ↓ > OS ↓ > CV ↑ > MO ↑). The good antibacterial effect against E. coli was also demonstrated [30,32] for RP and MO [50]. In the case of MO, a medium effect on E. coli was observed [51], while our studies are supported by Ferrente et al (2020) [15], who proved a promising effect of OS on three E. coli strains, with concentrations ranging from 31-250 µg/mL.…”
Section: Antimicrobial Activitysupporting
confidence: 85%
“…Higher values of phenolic compounds in the flowers (0.77 mg GAE/mL) were observed compared to syrup 60 • Brix (0.06 mg GAE/mL) and R. pseudoacacia syrup 70 • Brix (0.14 mg GAE/mL) [31]. Serbian RP showed values of 74.28 ± 1.73 for TPC (mg GAE/g) [29], while Arnold et al (2015) [32] reported a phenolic content of 20.55 ± 2.56 mg GAE/g in the OS extract.…”
Section: Chemical Composition Of Extractsmentioning
confidence: 89%
“…The lowest antioxidant capacity was observed for the subterranean parts sample collected from the Vatra Dornei extract, confirmed by all 3 methods used. In the literature, no quantification was found to be directly comparable through association of methodology and plant parts analyzed; however, the qualitative comparison of leaves (higher antioxidant capacity) and roots (lower antioxidant capacity) aligned our research with previous reports (summarized in the Supplementary Materials Section in Table S1) [12,14,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 85%
“…For P. japonicus leaf extracts, there was no large difference in antioxidant and anti-melanogenic activities according to the extraction method. The methanol extract of P. hybridus leaf contained higher level of TPC (122.61 mg GAE/g extract; Arnold et al, 2015) compared with P. japonicus leaf extract (Table 2). However, it has been shown that TPC in the methanol extract of P. japonicus was 218.32 mg GAE/g extract (Kim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%